Information Needs and Preference for Information Delivery Channels of Small and Medium-scale Enterprise Operators in Ghana - Larteley Adu, Theresa (Ghana Library Journal, 2008)
This study in vestigated the information needs and information seeking behaviour of SME operators in Ghana using a questionnaire (n = / 89), with a response rate of 47. I%. Over 50% of the respondents across all sub-sectors indicated an urgent need for information in all the business areas specified apart from land/premises, new staff and parent company. Gender of entrepreneur, educational background, ownership type and size of enterprise influenced different aspects of information needs, with gender influencing needs such as how to create better product and the educational background influencing information on export market and international/aws and regulations. The two most preferred means of obtaining information were SDI and online databases with thepossibility of conducting research in a documentation centre being the least preferred. Lack of adequate training for information specialists in entrepreneurship in Ghana might have accounted for the wide information needs gap in this study and calls for specialist training for business information practitioners in Ghana.